1991
DOI: 10.1111/j.1365-2044.1991.tb09360.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen delivery Systems–a comparison of two devices

Abstract: Summary Two low‐volume, variable performance oxygen delivery Systems were compared in conscious spontaneously breathing volunteers. Oropharyngeal oxygen concentrations were measured during periods of nose and mouth breathing. The Systems were studied at oxygen flow rates of 2 or 4 litres/minute. The performance of both Systems was similar under the test conditions but the nasal catheter is preferable in terms of cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Modern management of the sick patient involves the administration of oxygen in supposedly known concentrations. There are a many delivery systems commercially available whose performances are documented in the literature [1–8]. This is usually reported as the actual delivery from the system [3], the resultant inspired concentration of oxygen [1, 2, 4–9], or the arterial oxygenation achieved [9].…”
Section: Factors That Influence the Fio2 Delivered To A Patient By Omentioning
confidence: 99%
See 1 more Smart Citation
“…Modern management of the sick patient involves the administration of oxygen in supposedly known concentrations. There are a many delivery systems commercially available whose performances are documented in the literature [1–8]. This is usually reported as the actual delivery from the system [3], the resultant inspired concentration of oxygen [1, 2, 4–9], or the arterial oxygenation achieved [9].…”
Section: Factors That Influence the Fio2 Delivered To A Patient By Omentioning
confidence: 99%
“…From a physics perspective, the actual concentration of oxygen delivered is determined by the interaction between the delivery system and the patient's breathing pattern [4]. In contrast, most of the in vivo measurements that have been reported were carried out in normal subjects breathing at rest or trained to vary their tidal volumes [1–5, 7–18]. Several of these studies do point out that there are multiple factors which may compromise the performance of these devices and result in an effective F i o 2 that is less, or occasionally more, than that expected [4,7].…”
Section: Factors That Influence the Fio2 Delivered To A Patient By Omentioning
confidence: 99%
“…It has been reported that there are no significant differences in partial pressure of arterial carbon dioxide (PaCO 2 ) or oxygen saturation measured by pulse oximetry (SpO 2 ) when using various devices. 2,3 Such devices deliver a variable inspired oxygen concentration (FIO 2 ), especially in patients with chronic obstructive pulmonary disease or during the postoperative nocturnal period. 4 Not only do some patients find face masks uncomfortable or claustrophobic, but these masks also hinder speech.…”
Section: Méthodementioning
confidence: 99%
“…Fairfield et al concluded that both devices (mask and nasal catheter) delivered acceptable oxygen concentrations 7 . Bambridge found nasal catheters to be inadequate for patients requiring more than just routine oxygen therapy (above 50%) and, in their audit, the nasal catheter was unable to maintain adequate saturation levels 8 .…”
Section: Review Of the Researchmentioning
confidence: 99%